Extensions of intellectual property in Media Industry: The Korean case - Chaeyun Jang; Seongcheol Kim (International Telecommunications Society (ITS), 2023)
Content-based IP is the core engine to create a ripple effect in the media industry, distinctive from a prevalent distribution strategy of contents. Despite being the latecomer in the IP business, The Korean media industry recognizes the importance of a content-based IP extension strategy. Therefore, this case study aims to identify common factors of successful IP extension cases in Korea and propose a typology of successful IP extension paths. Utilizing the resource-based theory (RBV) and knowledge-based view (KBV) to redefine content based-IP as intangible resources owned by the media industry, this study proposes this theoretical framework for the case study of IP extension analysis. The case study of IP extensions in Korea, which emerged from the broadcasting, web comics and web novels, provides implications for media industries seeking content-based IP extension strategies.
Keywords: 330; IP(Intellectual property); Content-based IP; IP extension; Korean media industry; RBV (resource-based view); Case study